Dinamika Interaksi Sosial Mahasiswa Broken-home dengan Teman Sebaya di Perguruan Tinggi - Al Fitri Nur Hidayah; Evi Winingsih; Najlatun Naqiyah (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
Coming from an incomplete family background or a broken home can significantly impact the psychological and social development of college students. In college, these students face complex challenges in building social interactions with peers, who often serve as their primary support system. The dynamics of these interactions remain poorly understood. This study aims to describe and analyze the dynamics of social interactions between students from broken homes and their peers in college. Using a qualitative approach with descriptive analysis methods, this study involved four female students as subjects. Data were collected through in-depth interviews and analyzed using an interactive model. The results indicate that the interaction dynamics stem from unresolved emotional burdens from family circumstances, which drain their social energy. Furthermore, a behavioral paradox arises between the need for connection and self-protection mechanisms triggered by fear of vulnerability. Nevertheless, students demonstrate agency and resilience by developing active coping strategies. The culmination of this process is the transformation of friendship into a